Feasibility investigation of the accelerated skill acquisition program (ASAP): Insights into reach-to-grasp coordination of individuals with postacute stroke - Tretriluxana, Jarugool; Runnarong, Nuttakarn; Tretriluxana, Suradej; Prayoonwiwat, Naraporn; Vachalathiti, Roongtiwa; Winstein, Carolee (My University, 2013)
Background: Skill acquisition, capacity building, and motivational enhancements are the basis of the Accelerated Skill Acquisition Program (ASAP) and form the foundation for effective incorporation of the paretic upper extremity into life activities. This is the first phase I trial to deliver ASAP during the postacute interval in mildly to moderately impaired stroke survivors and to include an assessment of paretic reach-to-grasp (RTG) coordination using RTG task and cross-correlation analyses. Methods: Two baseline and posttreatment evaluations consisted of RTG actions, the Wolf Motor Function Test (WMFT), and the Stroke Impact Scale (SIS). An individualized arm therapy program using ASAP principles was administered for a total of 30 hours, 2 hours per day, for 2 to 4 days per week over 5 weeks. Dependent measures were kinematics of RTG actions, RTG coordination, total time score of WMFT, and stroke recovery score of SIS. Results: All participants tolerated ASAP well, and none reported any adverse effects during or after the protocol. When the 2 baseline evaluations were compared, there were no changes in any RTG kinematics or RTG coordination. In contrast, after 30 hours of ASAP, total movement time and deceleration time of RTG actions markedly decreased, maximum reach (transport) velocity strikingly increased, and time of maximum aperture was accomplished later. Additionally, the maximal RTG correlation coefficient increased with a shorter associated time lag. A similar pattern was observed for the clinical outcome measures of WMFT and SIS. Conclusions: The findings demonstrate the feasibility of using an ASAP protocol for patients 1 to 3 months post stroke. Under ASAP, WMFT tasks and RTG actions were performed faster with higher peak transport velocity and a more coordinated RTG pattern. The next step is to determine whether the immediate gains in the skilled RTG actions persist 6 months alter. © 2013 Thomas Land Publishers, Inc.
Keywords: motor learning; neural plasticity; reach-to-grasp coordination; task-oriented training